EFEKTIVITAS PENERAPAN APLIKASI MANAJEMEN LAPORAN KEUANGAN MASJID BERBASIS TEKNOLOGI INFORMASI ANDROID DALAM PENERAPAN HUKUM EKONOMI SYARIAH - Anggun Hutasuhut (Al Qadhi, 2023)
The implementation of financial report management applications based on Android information technology in mosques has become a significant innovation in the application of Shariah economic law. This research investigates the effectiveness of applying this information technology in managing mosque financial reports. An experimental research method was used involving the development of a specific Android application to record and track financial transactions in accordance with Shariah principles. The results indicate a significant improvement in the accuracy, speed, and reliability of financial reporting after the implementation of this application. Furthermore, the application enhances transparency and accountability in mosque financial management, thereby reinforcing the application of Shariah economic law in the context of mosque finances. Despite some challenges in adopting this technology, such as a lack of technological understanding, the benefits obtained are considerably greater. The implications of this study suggest that the use of information technology, such as the Android application, can enhance efficiency and compliance with Shariah economic principles in mosque financial management. The application of financial report management applications based on Android information technology in mosque financial management specifically focuses on implementing Shariah economic principles. This research explores the effectiveness of Android information technology in aiding the recording, reporting, and management of mosque finances in accordance with Shariah principles. The use of information technology in mosque financial management has significant implications for enhancing compliance with Shariah economic principles. This study highlights that the application of Android software in the context of mosque finances can make a significant contribution to Shariah-compliant fund management, with the potential to improve transparency, compliance, and efficiency in mosque financial management.